Understanding the Compensation of Nonprofit Executive Directors: Examining the Influence of Performance and Organizational Characteristics. Issue 3 (23rd January 2014) - Grasse, Nathan; Davis, Trenton; Ihrke, Douglas
Abstract In this study we aimed to provide a better understanding of executive compensation in nonprofit organizations. We examined factors including organizational size, market, subsector, organizational type, staffing level, and organizational performance as potential influences driving variation across the nonprofit sector. The models utilize data on the population of nonprofit organizations required to file Form 990 returns with the Internal Revenue Service in order to broadly examine compensation. The results indicate associations between various measures of performance and compensation in nonprofit orga‐nizations and also suggest that different types of nonprofits may be sensitive to different measures of performance.